2010
DOI: 10.1002/ajhb.20985
|View full text |Cite
|
Sign up to set email alerts
|

Body size and human energy requirements: Reduced mass‐specific total energy expenditure in tall adults

Abstract: Mammalian resting energy expenditure (REE) increases as approximately weight(0.75) while mass-specific REE scales as approximately weight(-0.25). Energy needs for replacing resting losses are thus less relative to weight (W) in large compared with small mammals, a classic observation with biological implications. Human weight scales as approximately height(2) and tall adults thus have a greater weight than their short counterparts. However, it remains unknown if mass-specific energy requirements are less in ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In Jamaican 7-8-year-old children, it was shown that a short-stature group had a reduced BMR when compared to a normal-stature group 35 . A hypothesis reported by Heymsfield, Chirachariyavej 12 indicates that relative to body weight and height, individuals differ in their proportions of heat-producing tissues, such as skeletal muscle and brain mass, an important determinant for BMR 12,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In Jamaican 7-8-year-old children, it was shown that a short-stature group had a reduced BMR when compared to a normal-stature group 35 . A hypothesis reported by Heymsfield, Chirachariyavej 12 indicates that relative to body weight and height, individuals differ in their proportions of heat-producing tissues, such as skeletal muscle and brain mass, an important determinant for BMR 12,36 .…”
Section: Discussionmentioning
confidence: 99%
“…A main motivation for the current study was to further our quantitative understanding of the mechanisms underlying energy expenditure scaling relations in humans, with implications for scaling relationships in mammals as a whole (Heymsfield, ; Heymsfield, Thomas, et al, ). Large animals and humans, characterized by body mass and height, respectively, have lower mass‐specific resting metabolic rates compared to their small counterparts (Heymsfield & Pietrobelli, ). One explanation for body size‐related variation in mass‐specific metabolic rate is variation in organ proportions with a shift in body composition with greater height to low metabolic rate components (ie, to a larger proportion of body weight as bone and SM bone [<~15 kcal/kg/d] and to a smaller proportion of brain, liver, and kidney [>200 kcal/kg/d]) (Heymsfield, Peterson, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The daily rate of energy expenditure is proportional to body weight, thus, subjects’ diets were personalized based on their body weights. In the current study design, weight change from energy flux imbalance was achieved from a combination of diet (restricted energy intake) and exercise (increased energy expenditure), together known as diet and exercise (D&E).…”
Section: Methodsmentioning
confidence: 99%